New Product Development: design of scales in the banana sector in Peru - Sánchez Ruíz, Eduardo Alonso (2013)
The standard models of scales do not satisfy the specific requirements for the Peruvian Agricultural condition, therefore generating unnecessary costs and times in the banana sector. The development process of new products focused in sustainability has allowed generating added value of labor and creativity by designing prototypes of scales that incorporate solar panels.